Technical Study of Natural Fibers from Banana Fronds as Boat Component Material in Inland Waterways - Wijaya, Vibra; Alamsyah, Alamsyah; Hijriah, Hijriah; Suardi, Suardi; Pawara, Muhammad Uswah (Indonesian Journal of Maritime Technology, 2024)
Many types of bananas are grown in Indonesia, indicating that it is one of the banana producing countries. Banana leaves are processed to make them stronger and more easily absorbed, so they are suitable as a composite mixture. Making banana stems as an alternative reinforcement for composite materials. Use ecologically safe substances and replace synthetic compounds. The aim of this research is to investigate the tensile strength and flexural strength of banana stem material as a composite fiber alloy in ship component materials in accordance with the review of the Indonesian Classification Bureau (BKI). The method used is experimental testing with a UTM machine according to ASTM D638-03 standards and ASTM D-790 standards. The results of the test experiments show that the tensile strength and flexural strength of banana stems as a composite and natural material are not yet suitable for use as boat component materials under water (hull skin construction), according to BKI's review, but can be used as an alternative composite material for boat component materials above the water line.